(untitled) (Research, Society and Development, 2022)
The aim of this study was to report a clinical case of oral squamous papilloma, addressing its clinical and histopathological aspects and clinical treatment approach. A 16-year-old female patient with an intellectual disability arrived at the Dental Specialties Center with the main complaint of “damaged teeth”. In the intraoral clinical examination, in addition to dental units compromised with caries disease, a lesion in the apex of the tongue, with a papillary aspect, measuring approximately 0.5 cm, normal color of the mucosa, sessile with well-defined edges was observed. Due to the close contact with the lower central incisors that were crowded, it was suggested as a diagnostic hypothesis of traumatic fibroma. Excisional biopsy was performed and the result of the anatomopathological examination was oral squamous papilloma. The family was instructed on the need for periodic follow-up to identify possible future oral lesions, referral of the patient to the Gynecologist, since she had never been to the specialist, and according to the mother, the daughter had not started sex, but had already been immunized against HPV. It should be noted that all persistent mouth lesions should be biopsied, as lesions that are apparently harmless can be diagnosed and require a more careful approach.